Peroxisomes are signaling platforms for antiviral innate immunity - Dixit, Evelyn; Boulant, Steeve; Zhang, Yijing; Lee, Amy S Y; Odendall, Charlotte; Shum, Bennett; Hacohen, Nir; Chen, Zhijian J; Whelan, Sean P; Fransen, Marc; Nibert, Max L; Superti-Furga, Giulio; et al. (Cell, 2010)
Peroxisomes have long been established to play a central role in regulating various metabolic activities in mammalian cells. These organelles act in concert with mitochondria to control the metabolism of lipids and reactive oxygen species. However, while mitochondria have emerged as an important site of antiviral signal transduction, a role for peroxisomes in immune defense is unknown. Here, we report that the RIG-I-like receptor (RLR) adaptor protein MAVS is located on peroxisomes and mitochondria. We find that peroxisomal and mitochondrial MAVS act sequentially to create an antiviral cellular state. Upon viral infection, peroxisomal MAVS induces the rapid interferon-independent expression of defense factors that provide short-term protection, whereas mitochondrial MAVS activates an interferon-dependent signaling pathway with delayed kinetics, which amplifies and stabilizes the antiviral response. The interferon regulatory factor IRF1 plays a crucial role in regulating MAVS-dependent signaling from peroxisomes. These results establish that peroxisomes are an important site of antiviral signal transduction.